Natural Environment Disclosures in the Annual Reports of Chinese Listed Entities - Qi, Y.; Taplin, Ross; Brown, Alistair (Sage Publications, 2012)
This paper analyzes the level of natural environment disclosure (NED) in the year ending 2007 annual reports of Chinese-listed companies. Using a simplified NED index that accommodates a developing country setting, the results show a low level of NED. Only 2% of sampled companies make disclosures for all eight basic environmental issues in the NED index. Larger companies and resource companies disclose significantly more NED. Clearly there is scope for Chinese regulators and entities to improve the reporting of natural environmental issues. Strategies are explored to consider how NED might be improved.